2022
DOI: 10.3390/ma15072585
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Shape Memory Effect of a Fe-Mn-Si-Cr-Ni Alloy through Shot Peening

Abstract: To improve the shape memory effect, the solutionized Fe-24Mn-6Si-9Cr-6Ni alloy was shot peened and subsequently annealed. The phase constituent was examined using the X-ray diffraction method. Microstructure evolution was characterized using an optical microscope and the electronic backscatter diffraction method, and the shape memory effect was evaluated using a bending test. The results show that α′-martensite and ε-martensite were introduced into the shot-peened surface layer. The α′-martensite remained afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Additionally, figures 5(a)-(c) demonstrate the varying effects of different SP parameters on the microstructure and grain refinement within the plastic deformation layer. Studies conducted by Yang Huanping et al [34] and Moradi Ali et al [35] have observed that SP treatment contributes to the refinement of the microstructure in materials such as Fe-24Mn-6Si-9Cr-6Ni alloy and Ti-6Al-4V alloy. In their pursuit of accurately predicting the relationship between SP parameters and grain size, Wang et al [36] even established a coupling model for this purpose.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, figures 5(a)-(c) demonstrate the varying effects of different SP parameters on the microstructure and grain refinement within the plastic deformation layer. Studies conducted by Yang Huanping et al [34] and Moradi Ali et al [35] have observed that SP treatment contributes to the refinement of the microstructure in materials such as Fe-24Mn-6Si-9Cr-6Ni alloy and Ti-6Al-4V alloy. In their pursuit of accurately predicting the relationship between SP parameters and grain size, Wang et al [36] even established a coupling model for this purpose.…”
Section: Resultsmentioning
confidence: 99%
“…where A Nb and A C are the atomic mass of Nb and C, respectively. Using equations (11) and (12), W e Nb and W e C can be calculated.…”
Section: Solubility Productmentioning
confidence: 99%
“…Given an initial composition of the Fe-Mn-Si-based shape memory alloys, the solubility product KSP of NbC at temperature T is determined through equation (10). The equilibrium weight fractions W e Nb and W e C are solved by equations (11) and (12). Then, the driving force G v D for nucleation can be calculated by equation (2).…”
Section: Simulation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…When SMAs are subjected to external force, a stress-induced martensite transformation occurs, and the macroscopic transformation is the deformation of the alloy. Martensite reverse transformation is activated when the temperature rises to A s , and the alloy can almost completely recover to its original shape when the temperature reaches above A f [15][16][17][18]. The SME is reflected in this process, as shown by the red curve in Figure 1.…”
Section: Introductionmentioning
confidence: 96%